Selected Decisions from the Federal Supreme Court Cassation Bench - Chane, Gizachew Silesh (Bahir Dar University Journal of Law, 2022)
This case report contains two Selected Decisions from the Federal Supreme Court Cassation Bench. The first one concerns the implication of failure in National Exit Exam of Law Schools. It raises the question of whether the requirement for fulfilment and certification of graduation is due while a candidate graduate has failed the exit exam. The Second case involves labor disputes in which the courts entertained whether daily workers are entitled to weekends and holidays payment whether they stay at work on such supposedly rest days.